PENGARUH EKSTRAK ETANOL DAUN MAHONI (Swietenia mahogani L.) SEBAGAI FUNGISIDA NABATI DALAM MENGENDALIKAN Colletotrichum acutatum PENYEBAB ANTRAKNOSA PADA CABAI MERAH (Capsicum annuum L.) - Awalliyah, Asty; Yulianty, Yulianty; Salman, Farisi; Bambang, Irawan (Universitas Islam Kadiri, 2024)
Colletotrichum acutatum is a fungal pathogen that causes anthracnose which usually attacks chilies. Generally, in controlling anthracnose disease.. The use of synthetic fungicides that are used for a long time can cause various harmful effects, especially on the environment. So other alternatives by using vegetable fungicide obtained from ethanol extract of mahogany leaves. This study aims to determine the effect of ethanol extract of mahogany leaves and determine the best concentration of ethanol extract mahogany leaves as vegetable fungicide in controlling Colletotrichum acutatum causes anthracnose disease in red chili (Capsicum annuum L.). This study used a completely randomized) design with seven concentrations of mahogany leaf extract, namely 0 %; 0.5 %; 1 %; 1.5 %; 2 %; 2.5 %; 3 %. Each treatment repeated four times. The data obtained were analyzed by ANOVA and continued with the Least Significant Difference (LSD) test with a level of 5 % (Î±= 5 %). The results showed that ethanol extract of mahogany leaves had a significant effect on mushroom colony diameter and fruit weight loss. However, it had no significant effect on disease severity and fruit weight loss. The best concentration of ethanol extract of mahogany leaves was shown in 1.5 % treatment.